2011
DOI: 10.1088/1742-6596/296/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Wall shear stress hot film sensor for use in gases

Abstract: -The dynamic response of a hot-wire anemometer: III. Voltage-perturbation versus velocity-perturbation testing for near-wall hot-wire/film probes B C Khoo, Y T Chew, C J Teo et al. Abstract. The purpose of this work is to present the construction and characterization of a wall shear stress hot film sensor for use in gases made with MEMS technology. For this purpose, several associated devices were used, including a constant temperature feedback bridge and a shear stress calibration device that allows the senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, the calibration coefficients A of different resistance sensors are different. The principle of the active heat insulation method is to utilize a double-layer structure to impede heat transfer to the substrate [12]. As shown in figure 2, the upper-layer heating resistor is placed in the flow field as a heat-sensitive unit and the lower-layer heating resistor is utilized as a heat-insulating unit.…”
Section: Working Principlementioning
confidence: 99%
“…Therefore, the calibration coefficients A of different resistance sensors are different. The principle of the active heat insulation method is to utilize a double-layer structure to impede heat transfer to the substrate [12]. As shown in figure 2, the upper-layer heating resistor is placed in the flow field as a heat-sensitive unit and the lower-layer heating resistor is utilized as a heat-insulating unit.…”
Section: Working Principlementioning
confidence: 99%
“…Inspired by the guard heater used in [5,6,19], Liu et al [14] demonstrated the uniqueness of calibration could be achieved by using a dual hot-film sensor consisted of a non-electric conductive membrane sandwiched in between two metal films. The two films were operated at a same temperature with a uncertainty of ±0.2 °C in the temperature difference.…”
Section: Introductionmentioning
confidence: 99%